The Pattern of Relation of Muhammadiyah and Parmusi: Pola Relasi Muhammadiyah dan Parmusi - Suwarno, Suwarno (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to reveal the pattern of relations between Muhammadiyah and the Indonesian Muslim Party (Parmusi). In this study, the author used the historical research method, following four steps. First, heuristics or collection of primary and secondary sources centered at the Muhammadiyah Central Library of Yogyakarta, the National Library of Jakarta, and the National Archives Office of the Republic of Indonesia (ANRI) Jakarta. Second, source criticism which includes external criticism to test the authenticity and internal criticism to determine the credibility of the source. Third, the interpretation or interpretation of historical facts resulting from the second step by conducting analysis and synthesis. Fourth, historiography or writing of historical work. The results showed that in the process of founding Parmusi in 1968, Muhammadiyah had played an important role as a midwife born in Parmusi. In the development of Parmusi until this party merged in the United Development Party (PPP) in 1973, Muhammadiyah's relations with Parmusi showed a more ideological rather than organizational relationship pattern.